Customers' Perception of Online Zakat Payment Between Government and Private Sector Employees - Noorhayati, Abd Halim (2011)
Zakat payment by online is one of the new approach in Malaysia. Know as an electronic payment or e-payment, the payment transaction through Internet network more easily and quickly without going to zakat counter. Becoming in developments of technology changes, are not left behind Majlis Agama Islam Perak varied zakat payment, with desire to ease customers implement this pillar of Islam. Beside that, zakat institution can increase their total zakat collection. In this study, was to see customer’s perceptions on zakat payment by online. 150 questionnaires have been distributed and only 130 can be collected. Moreover, the finding shows that four variables (perceived usefulness, perceived ease of use, perceived behavioral control and trust) have a low relationship to customers’ perception of zakat online payment.